'Only through unity': lessening the impact of cardiac diseases on cognitive function. (2nd September 2022) - Cowan, Helen
Abstract : In this quarterly column, Helen Cowan sheds some light on the lesser known area of cardiac nursing in care homes, looking at nurse-led diagnosis and management of cardiac conditions.